A sequence analysis of patterns in self-harm in young people with and without experience of being looked-after in care - Wadman, Ruth; Clarke, David; Sayal, Kapil; Armstrong, Miriam; Harroe, C.; Majumder, P.; Vostanis, Panos; Townsend, Ellen (Wiley, 2017)
Objectives: Young people in the public care system (‘looked-after’ young people) have high levels of self-harm. Design: This paper reports the first detailed study of factors leading to self-harm over time in looked-after young people in England, using sequence analyses of the Card Sort Task for Self-harm (CaTS). Methods: Young people in care (looked-after group: n = 24; 14-21 years) and young people who had never been in care (contrast group: n = 21; 13-21 years) completed the CaTS, describing sequences of factors leading to their first and most recent episodes of self-harm. Lag sequential analysis determined patterns of significant transitions between factors (thoughts, feelings, behaviours, events) leading to self-harm across six months. Results: Young people in care reported feeling better immediately following their first episode of self-harm. However, fearlessness of death, impulsivity and access to means were reported most proximal to recent self-harm. Although difficult negative emotions were salient to self-harm sequences in both groups, young people with no experience of being in care reported a greater range of negative emotions and transitions between them. For the contrast group, feelings of depression and sadness were a significant starting point of the self-harm sequence six months prior to most recent self-harm. Conclusions: Sequences of factors leading to self-harm can change and evolve over time, so regular monitoring and assessment of each self-harm episode is needed. Support around easing and dealing with emotional distress is required. Restricting access to means to carry out potentially fatal self-harm attempts, particularly for the young persons with experience of being in care, is recommended.